ADVERSE REACTIONS IN PLATELETPHERESIS DONORS IN CENTRAL CHEST INSTITUTE OF THAILAND - Mangkang, Chutima (Srinakharinwirot University Journal of Sciences and Technology, 2024)
This study was designed to review the incidence of adverse reactions occurred during and after in donors undergoing apheresis for platelet donation. Adverse reactions during and after the apheresis procedures were analyzed according to the following categories: (1) complications related to citrate toxicity; (2) fainting and (3) hyperventilation. From January to December 2020, a total of 477 plateletpheresis procedures were performed by Amicus blood cell separator (Fresenius Kabi) in Central Chest Institute of Thailand. This was performed and analyzed by medical technologist from data worksheet, separate by gender and age. The results show that: Of 477 plateletpheresis procedures, 160 (33.5%) were associated with adverse reactions. 158 (33.1%) of 447 donation-related adverse reactions involved citrate-related complications and 2 (0.4%) involved fainting but mostly mild symptoms. The overall donor reaction rate was not associated with age but associated with gender. The complications related to citrate toxicity occurred in female 31 (65.9%) from 47 procedures, in male 128 (29.7%) from 430 procedures. This was performed without oral calcium carbonate intake. The most common of adverse reaction rate in platelet apheresis donors is complications related to citrate toxicity, but generally mild and successful collections, compared with fainting or hyperventilation. Determining whether research founded that plateletpheresis donation by automated blood cell separator which contains anticoagulant ACD-A solution, be safe on the donors and no necessary to intake oral calcium carbonate.